Eviota brahmi n. sp. from Papua New Guinea, with a redescription of Eviota nigriventris (Teleostei: Gobiidae) - Greenfield, David W.; Tornabene, Luke (Zootaxa, 2014)
Greenfield & Randall (2011) described the gobiid fishes Eviota dorsogilva from Fiji and E. dorsopurpurea from Papua New Guinea as new species in what they termed the Eviota nigriventris complex. They also extended the range of E. nigriventris, type locality Banda Sea, to Milne Bay, Papua New Guinea. In the present paper, we describe their misidentified E. nigriventris from Papua New Guinea as a new species, E. brahmi, and redescribe E. nigriventris based on new material from near the type locality. The four species of this complex differ mainly in coloration, but are also shown to be distinct using mitochondrial and nuclear DNA.